I'd tell you I love you, but then I'd have to kill you - Carter, Ally (Disney/Hyperion, 2016)
As a sophomore at a secret spy school and the daughter of a former CIA operative, Cammie is sheltered from "normal teenage life" until she meets a local boy while on a class surveillance mission.